Integrin alpha 6 is upregulated and drives hepatocellular carcinoma progression through integrin α6β4 complex. Issue 6 (19th June 2022) - Zheng, Guixi; Bouamar, Hakim; Cserhati, Matyas; Zeballos, Carla R.; Mehta, Isha; Zare, Habil; Broome, Larry; Hu, Ruolei; Lai, Zhao; Chen, Yidong; Sharkey, Francis E.; Rani, Meenakshi; et al.
Abstract: Integrin α6 (ITGA6) forms integrin receptors with either integrin β1 (ITGB1) or integrin β4 (ITGB4). How it functions to regulate hepatocellular carcinoma (HCC) progression is not well‐elucidated. We found that ITGA6 RNA and protein expression levels are significantly elevated in human HCC tissues in comparison with paired adjacent nontumor tissues by RNA sequencing, RT‐qPCR, Western blotting and immunofluorescence staining. Stable knockdown of ITGA6 with different ITGA6 shRNA expression lentivectors significantly inhibited proliferation, migration and anchorage‐independent growth of HCC cell lines in vitro, and xenograft tumor growth in vivo. The inhibition of anchorage‐dependent and ‐independent growth of HCC cell lines was also confirmed with anti‐ITGA6 antibody. ITGA6 knockdown was shown to induce cell‐cycle arrest at G0/G1 phase. Immunoprecipitation assay revealed apparent interaction of ITGA6 with ITGB4, but not ITGB1. Expression studies showed that ITGA6 positively regulates the expression of ITGB4 with no or negative regulation of ITGB1 expression. Finally, while high levels of ITGA6 and ITGB4 together were associated with significantly worse survival of HCC patients in TCGA data set, the association was not significant for high levels of ITGA6 and ITGB1. In conclusion, ITGA6 is upregulated in HCC tumors and has a malignant promoting role in HCC cells through integrin α6β4 complex. Thus, integrin α6β4 may be a therapeutic target for treating patients with HCC. Abstract : What's new? Evidence suggests that integrins, which provide an adhesion mechanism between the intracellular and extracellular environments, serve an essential role in cancer progression. Of particular interest in cancer is integrin alpha 6 (ITGA6). In this study, ITGA6 was found to be significantly upregulated in human hepatocellular carcinoma (HCC). Increased ITGA6 expression was linked to increased ITGB4 expression and promotion of HCC malignancy, in complex with ITGB4. Elevated ITGA6 and ITGB4 expression was further associated with reduced patient survival. The findings suggest that the integrin α6β4 complex may be a therapeutic target for the treatment of patients with HCC.